Selected works of M.N. Roy : 1923-1927/ by M. N. Roy - Ray,Sibnarayan (ed.) (Delhi, 1988)
Volume II of the Selected Works presents a selection of his principal writings between 1923 and 1927. Many of these writings have not been available in print for a very long time as they were proscribed by the government immediately on publication. The volume includes the complete texts of his justly famous Political Letters and Future of Indian Politics, the Open Letter to J. R. Macdonald, his speeches at the Fifth Congress of the Comintern, a selection of his articles in The Vanguard, The Masses, Inprecor, and The Communist International, and his major speeches in China where he was sent as Chief Comintern delegate in 1927. By 1926, Roy was at the height of his Comintern carcer-a member of its Executive Committee and Presidium, its Secretariat and Orgburo, Chairman of Eastern Commission and Joint Secretary of the Chinese Commission.
Keywords: "Roy, M.N."